2018
DOI: 10.3892/ol.2018.9625
|View full text |Cite
|
Sign up to set email alerts
|

Su Yang Decoction induces human colon carcinoma cell apoptosis by activating caspases

Abstract: Su Yang Decoction (SYD) is a popular healthcare product comprised of various brassicaceous vegetables known to exhibit anticancer activity. However, the effects of SYD on tumor growth, following its combination with brassicaceous vegetables into a compound formula, require further investigation. In the present study, a quality control of SYD was subjected to high-performance liquid chromatography for the quantitative and qualitative determination of sulforaphane, the main anticancer component of SYD. SYD inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Caspase 3 worked as a key executioner during the latest stages of apoptosis both by extrinsic and intrinsic pathways, which can interact with both Caspase 8 and Caspase 9. 44 The inhibition of Caspase 8 and Caspase 9 proteins in the receptor-mediated pathway and mitochondrial pathway abolished the LCB induced apoptosis significantly. PUMA as an essential intermediate during p53dependent apoptosis can activate the Bax and mitochondrial outer membrane permeabilization.…”
Section: ■ Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Caspase 3 worked as a key executioner during the latest stages of apoptosis both by extrinsic and intrinsic pathways, which can interact with both Caspase 8 and Caspase 9. 44 The inhibition of Caspase 8 and Caspase 9 proteins in the receptor-mediated pathway and mitochondrial pathway abolished the LCB induced apoptosis significantly. PUMA as an essential intermediate during p53dependent apoptosis can activate the Bax and mitochondrial outer membrane permeabilization.…”
Section: ■ Discussionmentioning
confidence: 96%
“…In return, activated Caspase 9 can process the downstream caspases, such as Caspase 3. Caspase 3 worked as a key executioner during the latest stages of apoptosis both by extrinsic and intrinsic pathways, which can interact with both Caspase 8 and Caspase 9 . The inhibition of Caspase 8 and Caspase 9 proteins in the receptor-mediated pathway and mitochondrial pathway abolished the LCB induced apoptosis significantly.…”
Section: Discussionmentioning
confidence: 99%
“…After Bak is released in cells subjected to internal stimulation, the mitochondria are destroyed to facilitate the release of cytochrome c, which further contributes to the activation of Caspase9 [50]. It has been reported that activated Caspase 9 is capable of further activating downstream Caspase 3, which interacts with Caspase8 and Caspase9 through the extrinsic and intrinsic pathways and induces apoptosis [51]. All of the above results suggest that the apoptosis of HepG2 cells induced by JMFs exposure may be achieved by affecting the expression regulation of related proteins in the extrinsic and intrinsic pathways (Figure 11).…”
Section: Materials and Chemicalsmentioning
confidence: 99%